THE EFFECTIVENESS OF POSTPARTUM YOGA ON UTERINE INVOLUTION AMONG POSTPARTUM WOMEN IN INDONESIA - Ni Putu Dian Ayu Anggraeni; Lucky Herawati; Melyana Nurul Widyawati (Alta Dharma Publisher, 2019)
Sub uterine involution is one of the pathological symptoms of the postpartum period, which causes complications. This is indicated by the size of the fundus uterine, which is greater than the normal size and elongated outflow of lochia. One of the non-pharmacological methods for preventing sub uterine involution is postpartum yoga which focuses on physical and breathing exercises, strengthening of the pelvic floor muscles, and relaxation of autosuggestions. The study aimed to analyze the effectiveness of postpartum yoga on uterine involution. A quasi-experimental, pre-test and post-test with the control group was applied in this study. Thirty-eight postpartum women received postpartum yoga as the intervention group. The control group was comprised of 19 women. The gain score of uterine involution in the intervention group was 9.14 ± 1.27 and in the control group 7.20 ± 1.11. The Cohen’s effect size test is 1.63. The result of the mann whitney test showed that there was a significant difference between the intervention group and the control group with p value 0,000. The result of determination (R Square), postpartum yoga had an effect of 40.3% on uterine involution after being controlled simultaneously with parity, frequency of breastfeeding, and anxiety. Postpartum yoga is effective to strengthen the uterine muscles, facilitate blood circulation, and stimulate neurohormonal so it could accelerate uterine involution. Further studies could measure of fundus uterine daily. Future researchers can develop postpartum yoga research with other variables such as anxiety, urinary incontinence, quality of life for postpartum women, and hormonal variables including oxytocin, endorphins, and cortisol. Keywords: postpartum yoga, postpartum period, postpartum exercise, uterine involution